ERYTHROCYTE PROFILE OF DETECTION DOGS AT THE STATE POLICE OF THE REPUBLIC OF INDONESIA MALANG CITY POLICE RESOR - Milena, Lona; Widyastuti, Srikayati; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2023)
The detection dog is one of the animals that assists the task of the Indonesian National Police in maintaining and securing the order of the Indonesian state. The tasks assigned to detection dogs are to find explosives, drug tracking operations, security operations and look for victims of natural disasters such as landslides to earthquakes. Due to environmental factors that are quite extreme and heavy affect the stress level of the bloodhound itself, environmental conditions greatly affect the picture of blood values. Therefore, the results of the health examination of the erythrocyte profile are needed. This research uses descriptive observational research method. The object used in this study was the entire population of Malang City Police's detection dogs. Blood was taken and then examined using a hematology analyzer machine and then compared with hematology standards and then analyzed. From the studies that have been done, it was concluded that all samples showed anemia with the results of various examination values, and are likely caused by poor quality feed and water. For this reason, it is necessary to carry out further examinations such as parasitic examinations, radiology, and blood chemistry.